Study of rheological and textural properties of emulsion ointment bases using modern emulsifiers - Zuikina, Elizabet; Buriak, Marina; Zuikina, Svitlana (Annals of Mechnikov's Institute, 2023)
Introduction. Dermatological diseases are not only a medical, but also a social problem, which significantly worsens the quality of life of people suffering from them. Emulsion-based ointments are the most adapted to human skin medicinal form in extemporaneous practice. They have high therapeutic efficiency and satisfactory consumer properties due to the presence of two phases at once, are able to provide improved diffusion of active pharmaceutical ingredients (API), maintain optimal concentration in the area of ​​application, have high adhesive properties, which allows them to be well distributed on the skin; provide close contact with tissues and high bioavailability of API, have an immediate or, if necessary, prolonged effect of the drug. In view of the above, the development of new modern emulsion bases will make it possible to solve a number of urgent issues: to expand the range of effective extemporaneous MLF for use in dermatology, to individualize the approach to the patient and to ensure an increase in the quality of life of patients. The purpose of this work there was a textural analysis of samples of emulsion ointment bases, designed to replace the vaseline base, on which ointments are traditionally made in pharmacies. The composition of the foundations was chosen based on the results of previous research. Materials and methods.The following emulsifiers were chosen for the study: Olivem 1000 ® (Cetearyl Olivate / Sorbitan Olivat) (Hallstar) and Emulpharma 1000 (Cetearyl alcohol, Glyceryl stearate, Sorbitan stearate, Cetearyl glucoside). As oil, corn oil was chosen for the oil phase. Steady shear behavior. Rheological studies were performed on a BROOKFIELD HB DV-ΙΙ PRO viscometer (USA). Textural properties. The tests were carried out using a TA-XT2 texturometer (Stable Micro Systems, UK) Back Extrusion Cell (A / BE). Results and discussion. Analyzing the obtained data, it can be seen that the quantitative indicators differ slightly in terms of the ratio both within one sample when the temperature changes and between sample No. 1 (25 °C) and No. 1 (32 °C) in comparison with sample No. 1 (25 °C) and No. 1 (32 °C). Also, when the samples were measured three times, the value of the standard deviation was greater in sample No. 1 both at 25 and 32 °C. These data demonstrate that the emulsifier Emulpharma 1000 is more stable to mechanical and temperature effects on the emulsion system. Conclusion.The results of the study of the rheological and textural properties of the samples showed that the behavior of the developed emulsion bases did not change significantly, however, in the comparative analysis of all parameters and their standard deviation values, sample No. 2 using Emulpharma 1000 had more acceptable values.